"Eu vim para trazer a minha ausência": considerações sobre a produção de sujeitos em intervenções institucionais da educação, saúde e justiça - Elisana Nascimento Santos (2018)
In an institutional context of three distinct bodies of knowledge, in this case, Education, Justice and Health, more specifically, Mental Health, this research aimed to understand how a subject can be produced by such context, taking as theoretical reference the Psychoanalysis. When we inquire about a possible "Production of Subjects", we refer to possible subjective impacts resulting from the symbolic marks arising from the interventions suffered in the services for which these Subjects are served. Thus, we question whether the subjects are also formed by the institutional interventions that suffer when they are referred and followed, in this study, in the paths covered by the School, Justice Forum and CAPSi. Starting from the hypothesis that the concept of the subject worked by the Freudian Psychoanalysis points us to a subjective constitution that, although it is given to each person through singular psychic processes, is necessarily marked by the relations established with the other, be it familial or social, we seek to trace a methodological path that brings us closer to our object of research recognized, a priori, only by the daily practice of work. Thus, we carry out a collection of information, through a documentary survey in medical records and, in addition, we describe a case to demonstrate the modus operandi of the institutions before a specific subject. We analyzed the identification through the symptom as a possibility of link between the subjects in the context of the services emphasized here, recognizing the opposition as a possible symptom of being produced by the subjects in this study. We find it difficult to answer the question of this research, since we have found Mental Health, Education and Justice as classic institutions that do not seem to fit as Ideals of Self for most subjects, in order to promote the establishment of emotional bonds investment by identification to its precepts. We conclude that the symptom of the opposition can represent an affection addressed to the institutions, as a symptomatic response, to denounce a protest of the subjects in front of the ideologically transmitted civilizational ideals in the contemporaneity